Tick Infestation and Molecular Detection of Tick-Borne Pathogens from Indian Long-Eared Hedgehogs (Hemiechinus collaris) in Pakistan - Shahzad Ali; Michael E. von Fricken; Asima Azam; Ahmad Hassan; Nora G. Cleary; Kiran Iftikhar; Muhammad Imran Rashid; Abdul Razzaq (Animals)
Hedgehogs can act as reservoirs for the transmission of tick-borne pathogens (TBPs) to domestic livestock, wild animals, and humans. Understanding host–tick dynamics is essential to evaluate the impact of TBPs. This study was conducted in Pakistan and aimed to determine the prevalence and species of TBPs in the blood and ticks of Indian long-eared hedgehogs captured from various environments. A total of 64 hedgehogs were captured to check for tick infestation. Tick species were identified morphologically and molecularly including ITS-2 region amplification by PCR and subsequent Sanger sequencing. Moreover, TBPs were identified in both ticks and the blood of hedgehogs through conventional PCR and sequencing, targeting the regions msp1b, 18S rRNA, and cytb for Anaplasma spp., Babesia spp., and Theileria spp., respectively. Out of 64 hedgehogs, 16 (25%) were found to be infested with ticks. Morphological and molecular analysis identified all 109 collected ticks as Rhipicephalus turanicus. Only one hedgehog (6.2%) was infected with A. marginale. From the tick samples, 3.7% tested positive for Theileria lestoquardi, 2.8% for Anaplasma marginale, and another 2.8% for Babesia bigemina. This study provides critical insights into circulating TBPs in this region and what possible role hedgehogs might play in disease maintenance for Anaplasma marginale while identifying multiple pathogens that are of concern to human and animal health.